The Influence of Ease of use, Service Quality, and Price on Purchasing Decisions in the Goseh Application through Goman's Features as a New Startup in Tanah Karo - Devika Sari; Ainun Mardhiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Consumer decisions in choosing and purchasing a brand cannot be separated from various factors, such as ease of use, service quality, and price. This research aims to measure the influence of ease of use, service quality, and price both partially and simultaneously on purchasing decisions in the Goseh application through the GoMan feature as a new startup in Tanah Karo. The form of research used is quantitative research with an associative approach. The data analysis methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing processed with IBM SPSS V.26. The research results show that the variables ease of use, service quality, and price have a positive and significant effect, both partially and simultaneously, on purchasing decisions in the Goseh application through the GoMan feature.